Ajaran Resiliensi dalam Kisah al-Qur’an dan Urgensinya bagi Single Mother Era Modern : Kajian Tematik Q.S Al-Qashash [28]: 7-13 - Nisa, Afdilla (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to explore the teachings of resilience in the story of Prophet Musa's mother as presented in the Qur'an, specifically Q.S Al-Qashash [28]: 7-13, and its urgency for single mothers in the modern era. This narrative contains values of steadfastness, trust in Allah, and strategies to face life's challenges that are relevant to single mothers. Through a thematic approach, this research identifies elements of resilience that can be applied in the daily lives of single mothers. The analysis is conducted using thematic interpretation methods and linked to contemporary social contexts. The findings reveal that the resilience values taught through the story of Prophet Musa's mother can provide inspiration and practical guidance for single mothers in facing various life challenges, such as overcoming economic difficulties, independently educating children, and maintaining psychological well-being. In conclusion, the teachings of resilience in the Qur'an are relevant and significant in supporting single mothers to lead more meaningful and productive lives.